Assessment of the Representative Payee Program of the Social Security Administration: Letter Report - National Research Council (The National Academies Press, 2005)
Keywords: Behavioral and Social Sciences

Estimating the Contributions of Lifestyle-Related Factors to Preventable Death: A Workshop Summary - Institute of Medicine (The National Academies Press, 2005)
This report is the summary of a workshop held by The Institute of Medicine (IOM) of the National Academy of Science December 13-14, 2004 to estimate the contributions of lifestyle-related factors to preventable death. The summary of this workshop includes presentations from experts in statistical design, epidemiology, quality-of-life measures, communication, and public policy and discussions among the participants. Panels of experts addressed the following topics: methodological issues when estimating the public health burden of lifestyle factors; estimating "attributable risk" in practice; alternative ways of measuring the health burden; and public policy issues.
Keywords: Health and Medicine

The Changing Transitions to Adulthood in Developing Countries: Selected Studies - National Research Council (The National Academies Press, 2005)
Serving as a companion to Growing Up Global, this book from the National Research Council explores how the transition to adulthood is changing in developing countries in light of globalization and what the implications of these changes might be for those responsible for designing youth policies and programs. Presenting a detailed series of studies, this volume both complements its precursor and makes for a useful contribution in its own right. It should be of significant interest to scholars, leaders of civil society, and those charged with designing youth policies and programs.
Keywords: Behavioral and Social Sciences

Measuring Research and Development Expenditures in the U.S. Economy - National Research Council (The National Academies Press, 2005)
This report examines the portfolio of research and development (R&D) expenditure surveys at the National Science Foundation (NSF), identifying gaps and weaknesses and areas of missing coverage. The report takes an in-depth look at the definition of R&D, the needs and potential uses of NSF’s R&D data by a variety of users, the goals of an integrated system of surveys and other data collection activities, and the quality of the data collected in the existing Science Resources Statistics surveys.
Keywords: Industry and Labor; Behavioral and Social Sciences; Surveys and Statistics

Cost-Benefit Analysis of Providing Non-Emergency Medical Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Transit Cooperative Research Program (TCRP) Web-Only Document 29: Cost-Benefit Analysis of Providing Non-Emergency Medical Transportation (NEMT) examines the relative costs and benefits of providing transportation to non-emergency medical care for individuals who miss or delay healthcare appointments because of transportation issues. The report includes a spreadsheet to help local transportation and social service agencies conduct their own cost-benefit analyses of NEMT tailored to the local demographic and socio-economic environment. The executive summary of the report is available as Research Results Digest 75.
Keywords: Transportation and Infrastructure

Firearms and Violence: A Critical Review - National Research Council (The National Academies Press, 2005)
For years proposals for gun control and the ownership of firearms have been among the most contentious issues in American politics. For public authorities to make reasonable decisions on these matters, they must take into account facts about the relationship between guns and violence as well as conflicting constitutional claims and divided public opinion. In performing these tasks, legislators need adequate data and research to judge both the effects of firearms on violence and the effects of different violence control policies.
Keywords: Behavioral and Social Sciences; Health and Medicine

Assessing the Quality of Cancer Care: An Approach to Measurement in Georgia - Institute of Medicine; National Research Council (The National Academies Press, 2005)
Shortly after 1998, leading members of Georgia's government, medical community, and public-spirited citizenry began considering ways in which some of Georgia's almost $5 billion, 25-year settlement from the tobacco industry's Master Settlement Agreement with the 50 states could be used to benefit Georgia residents. Given tobacco's role in causing cancer, they decided to create an entity and program with the mission of making Georgia a national leader in cancer prevention, treatment, and research. This new entity--called the Georgia Cancer Coalition, Inc. (GCC)-- and the state of Georgia subsequently began implementing a far-reaching state cancer initiative that includes five strategic goals: (1) preventing cancer and detecting existing cancers earlier; (2) improving access to quality care for all state residents with cancer; (3) saving more lives in the future; (4) training future cancer researchers and caregivers; and (5) turning the eradication of cancer into economic growth for Georgia. Assessing the Quality of Cancer Care identifies a set of measures that could be used to gauge Georgia's progress in improving the quality of its cancer services and in reducing cancer-related morbidity and mortality.
Keywords: Health and Medicine

Public Financing and Delivery of HIV/AIDS Care: Securing the Legacy of Ryan White - Institute of Medicine (The National Academies Press, 2005)
Each year it is estimated that approximately 40,000 people in the U.S. are newly infected with HIV. In the late 1990s, the number of deaths from AIDS dropped 43% as a result of highly active antiretroviral therapy. Unfortunately, the complex system currently in place for financing and delivering publicly financed HIV care undermines the significant advances that have been made in the development of new technologies to treat it. Many HIV patients experience delays in access to other services that would support adhering to treatment. As a result, each year opportunities are missed that could reduce the mortality, morbidity, and disability suffered by individuals with HIV infections. Public Financing and Delivery of HIV/AIDS Care examines the current standard of care for HIV patients and assesses the extent the system currently used for financing and delivering care allows individuals with HIV to actually receive it. The book recommends an expanded federal program for the treatment of individuals with HIV, administered at the state level. This program would provide timely access and consistent benefits with a strong focus on comprehensive and continuous care and access to antiretroviral therapy. It could help improve the quality of life of HIV/AIDS patients, as well as reduce the number of deaths among those infected.
Keywords: Health and Medicine

Enhancing the Community College Pathway to Engineering Careers - National Academy of Engineering; National Research Council (The National Academies Press, 2005)
Community colleges play an important role in starting students on the road to engineering careers, but students often face obstacles in transferring to four-year educational institutions to continue their education. Enhancing the Community College Pathway to Engineering Careers, a new book from the National Academy of Engineering and the National Research Council, discusses ways to improve the transfer experience for students at community colleges and offers strategies to enhance partnerships between those colleges and four-year engineering schools to help students transfer more smoothly. In particular, the book focuses on challenges and opportunities for improving transfer between community colleges and four-year educational institutions, recruitment and retention of students interested in engineering, the curricular content and quality of engineering programs, opportunities for community colleges to increase diversity in the engineering workforce, and a review of sources of information on community college and transfer students. It includes a number of current policies, practices, and programs involving community college–four-year institution partnerships.
Keywords: Education; Engineering and Technology

Decreasing Energy Intensity in Manufacturing: Assessing the Strategies and Future Directions of the Industrial Technologies Program - National Research Council (The National Academies Press, 2005)
The U.S. Department of Energy (DOE) has supported the Industrial Technologies Program (ITP) for more than a decade. This program supports R&D into energy efficiency technologies designed to decrease the energy intensity of the U.S. industrial sector. The focus in on seven energy-intensive industries—aluminum, chemicals, forest products, glass, metal casting, mining, and steel—known as the Industries of the Future (IOF). DOE asked the NRC for a review of this program including an evaluation of the ITP strategic plan, an evaluation of the technical quality of individual subprogram plans, and the prospective value of the multi-year program plan. This report presents the results of that review. It contains an assessment of the ITP strategy, of how effective it is being implemented, and the likelihood of achieving program goals. It also provides conclusions about the quality of the subprograms and recommendations about how to strengthen the subprograms and the overall program.
Keywords: Engineering and Technology; Energy and Energy Conservation; Industry and Labor

Growing Up Global: The Changing Transitions to Adulthood in Developing Countries - National Research Council; Institute of Medicine (The National Academies Press, 2005)
The challenges for young people making the transition to adulthood are greater today than ever before. Globalization, with its power to reach across national boundaries and into the smallest communities, carries with it the transformative power of new markets and new technology. At the same time, globalization brings with it new ideas and lifestyles that can conflict with traditional norms and values. And while the economic benefits are potentially enormous, the actual course of globalization has not been without its critics who charge that, to date, the gains have been very unevenly distributed, generating a new set of problems associated with rising inequality and social polarization. Regardless of how the globalization debate is resolved, it is clear that as broad global forces transform the world in which the next generation will live and work, the choices that today's young people make or others make on their behalf will facilitate or constrain their success as adults. Traditional expectations regarding future employment prospects and life experiences are no longer valid. Growing Up Global examines how the transition to adulthood is changing in developing countries, and what the implications of these changes might be for those responsible for designing youth policies and programs, in particular, those affecting adolescent reproductive health. The report sets forth a framework that identifies criteria for successful transitions in the context of contemporary global changes for five key adult roles: adult worker, citizen and community participant, spouse, parent, and household manager.
Keywords: Behavioral and Social Sciences

Simplified Shear Design of Structural Concrete Members - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 549: Simplified Shear Design of Structural Concrete Members examines development of practical equations for design of shear reinforcement in reinforced and prestressed concrete bridge girders. The report also includes recommended specifications, commentary, and examples illustrating application of the specifications. NCHRP Web-Only Document 78 contains extensive supporting information, including a database that can be used to compare the predictions from the recommended procedures to existing design procedures.
Keywords: Transportation and Infrastructure

Precision Estimates for AASHTO Test Method T308 and the Test Methods for Performance-Graded Asphalt Binder in AASHTO Specification M320 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Web Document 71: Precision Estimates for AASHTO Test Method T308 and the Test Methods for Performance-Graded Asphalt Binder in AASHTO Specification M320 includes the results of Phase 3 of NCHRP 9-26, in which data from the AMRL Proficiency Sample Program (PSP) are used to create or update precision estimates for a variety of test methods. These include those methods specified in AASHTO Standard Specification M320, “Performance-Graded Asphalt Binder,” and AASHTO Standard Test Method T308, “Determining the Asphalt Binder Content of Hot-Mix Asphalt (HMA) by the Ignition Method.” The report from Phase 1 of Project 9-26, which was published as NCHRP Web Document 54, includes precision estimates of selected volumetric properties of HMA using non-absorptive aggregates. The report from Phase 2, which was published as NCHRP Web Document 66, discusses the results of an investigation into the cause of variations in HMA bulk specific gravity test results using non-absorptive aggregates.
Keywords: Transportation and Infrastructure

Population, Land Use, and Environment: Research Directions - National Research Council (The National Academies Press, 2005)
Population, Land Use, and Environment: Research Directions offers recommendations for future research to improve understanding of how changes in human populations affect the natural environment by means of changes in land use, such as deforestation, urban development, and development of coastal zones. It also features a set of state-of-the-art papers by leading researchers that analyze population-land useenvironment relationships in urban and rural settings in developed and underdeveloped countries and that show how remote sensing and other observational methods are being applied to these issues. This book will serve as a resource for researchers, research funders, and students.
Keywords: Behavioral and Social Sciences; Earth Sciences

Centerline Rumble Strips - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 339: Centerline Rumble Strips (CLRS) examines current design, installation, configuration, dimension, and visibility issues associated with CLRS. The report addresses the need for guidance on warrants, benefits, successful practices, and concerns such as external noise and the reduced visibility of centerline striping material. Also addressed are pavement deterioration, ice buildup in the grooves, adverse impact on emergency vehicles, and the effect of CLRS on bicyclists. Particular attention was paid to available before-and-after CLRS installation crash data to document the safety aspects of CLRS and the availability of policies, guidelines, warrants, and costs regarding their use and design.
Keywords: Transportation and Infrastructure

Operational Differences and Similarities Among the Motorcoach, School Bus, and Trucking Industries - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 6: Operational Differences and Similarities Among the Motorcoach, School Bus, and Trucking Industries is designed as a single resource for information on profiles, safety statistics, and general business operations for these three commercial vehicle industries.
Keywords: Transportation and Infrastructure

Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate - Institute of Medicine (The National Academies Press, 2005)
Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. This new report, the sixth in a series of reports presenting dietary reference values for the intakes of nutrients by Americans and Canadians, establishes nutrient recommendations on water, potassium, and salt for health maintenance and the reduction of chronic disease risk. Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate discusses in detail the role of water, potassium, salt, chloride, and sulfate in human physiology and health. The major findings in this book include the establishment of Adequate Intakes for total water (drinking water, beverages, and food), potassium, sodium, and chloride and the establishment of Tolerable Upper Intake levels for sodium and chloride. The book makes research recommendations for information needed to advance the understanding of human requirements for water and electrolytes, as well as adverse effects associated with the intake of excessive amounts of water, sodium, chloride, potassium, and sulfate. This book will be an invaluable reference for nutritionists, nutrition researchers, and food manufacturers.
Keywords: Food and Nutrition

Analytical Tools for Asset Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 545: Analytical Tools for Asset Management examines two tools developed to support tradeoff analysis for transportation asset management. The software tools and the accompanying documentation are designed to help state departments of transportation and other transportation agencies identify, evaluate, and recommend investment decisions for managing the agency’s infrastructure assets.The software tools associated with NCHRP Report 545 are available in an ISO format. Links to instructions on buring an .ISO CD-ROM and the download site for the .ISO CD-ROM are below.Help on Burning an .ISO CD-ROM ImageDownload the NCHRP CRP-CD-57.ISO CD-ROM Image
Keywords: Transportation and Infrastructure

The Smallpox Vaccination Program: Public Health in an Age of Terrorism - Institute of Medicine (The National Academies Press, 2005)
December 13, 2002, the president of the United States announced that smallpox vaccination would be offered to some categories of civilians and administered to members of the military and government representatives in high-risk areas of the world. The events that precipitated that historic announcement included a series of terrorist attacks during the 1990s, which culminated in the catastrophic events of 2001.
Keywords: Conflict and Security Issues; Health and Medicine

Improving Data to Analyze Food and Nutrition Policies - National Research Council (The National Academies Press, 2005)
Several changes in the United States over the past two decades have implications for diet, nutrition, and food safety, including patterns of food consumption that have produced an increase in overweight and obese Americans and threats to food safety from pathogens and bioterrorism. The changes raise a number of critical policy and research questions: How do differences in food prices and availability or in households' time resources for shopping and food preparation affect what people consume and where they eat? How do factors outside of the household, such as the availability of stores and restaurants, food preparation technology, and food marketing and labeling policies, affect what people are consuming? What effects have food assistance programs had on the nutritional quality of diets and the health of those served by the programs? Where do people buy and consume food and how does food preparation affect food safety?
Keywords: Food and Nutrition; Behavioral and Social Sciences; Surveys and Statistics